Towards a diachronic perspective on Andean ethnohistorical and kinship, linearity and ayllu - Arana Bustamante, Luis (2014)
This study focus in some basic aspects in Andean studies to precise the nature of Qhapaq ayllu-the royal caste or nobility properly said of precolonial Inka-. From an ethnohistorian point of view, I precise here some related concepts as groups of filiation in Andean parenthood and kinship, the ayllu, and the ‘houses’ and royal houses. e theme is treated in somewhat theoretical way for conceptual aclaration and expanded study of colonial transformation of both social institution and social concept of Qhapaq aylluas royal house. The final stage of these institutions already mentioned were the “noble houses” of XVIIIth century documents. This study has the aim to clear and expand the posibilities of interpretation of huge material in existence.